Toward Worldwide Hepcidin Assay Harmonization: Identification of a Commutable Secondary Reference Material. (6th January 2020) - van der Vorm, Lisa N; Hendriks, Jan C M; Laarakkers, Coby M; Klaver, Siem; Armitage, Andrew E; Bamberg, Alison; Geurts-Moespot, Anneke J; Girelli, Domenico; Herkert, Matthias; Itkonen, Outi; Konrad, Robert J; Tomosugi, Naohisa; et al.
Abstract: BACKGROUND: Absolute plasma hepcidin concentrations measured by various procedures differ substantially, complicating interpretation of results and rendering reference intervals method dependent. We investigated the degree of equivalence achievable by harmonization and the identification of a commutable secondary reference material to accomplish this goal. METHODS: We applied technical procedures to achieve harmonization developed by the Consortium for Harmonization of Clinical Laboratory Results. Eleven plasma hepcidin measurement procedures (5 mass spectrometry based and 6 immunochemical based) quantified native individual plasma samples (n = 32) and native plasma pools (n = 8) to assess analytical performance and current and achievable equivalence. In addition, 8 types of candidate reference materials (3 concentrations each, n = 24) were assessed for their suitability, most notably in terms of commutability, to serve as secondary reference material. RESULTS: Absolute hepcidin values and reproducibility (intrameasurement procedure CVs 2.9%–8.7%) differed substantially between measurement procedures, but all were linear and correlated well. The current equivalence (intermeasurement procedure CV 28.6%) between the methods was mainly attributable to differences in calibration and could thus be improved by harmonization with a common calibrator. Linear regression analysis and standardized residuals showed that a candidate reference material consisting of native lyophilized plasma with cryolyoprotectant was commutable for all measurement procedures. Mathematically simulated harmonization with this calibrator resulted in a maximum achievable equivalence of 7.7%. CONCLUSIONS: The secondary reference material identified in this study has the potential to substantially improve equivalence between hepcidin measurement procedures and contributes to the establishment of a traceability chain that will ultimately allow standardization of hepcidin measurement results.